A Risk Score Including Carotid Plaque Inflammation and Stenosis Severity Improves Identification of Recurrent Stroke - Kelly, Peter J (LIPPINCOTT WILLIAMS & WILKINS, 2021)
10.1161/STROKEAHA.119.027268